Massive sinus of Valsalva aneurysm with an associated bicuspid aortic valve: A rare clinical image - English Kevan (Sciendo, 2024)
A sinus of Valsalva aneurysm is a rare cardiac anomaly characterized by an abnormal dilatation of the aortic root. This occurs due to a weakened elastic lamina at the junction of the aortic media and the annulus fibrosus. The aneurysm can be congenital or acquired and comprises up to 3.5% of all congenital cardiac defects. Due to the aneurysm's physiologic function and location, it can present significant clinical consequences in both the rupture and unruptured state. We present the case of a middle-aged male with no significant medical history who was found to have a massive unruptured sinus of Valsalva aneurysm. He was treated surgically with no postoperative complications.